2015
DOI: 10.1016/j.compstruct.2014.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on mechanical behavior of FRP-to-steel adhesively-bonded joint under combined loading-part 1: Before hygrothermal aging

Abstract: a b s t r a c tDue to various advantages of fiber-reinforced polymer (FRP) decks, the FRP-steel composite girder system is being increasingly used in new bridge constructions as well as rehabilitation projects for old bridges. This paper presents the first part of the research project, focusing on mechanical behaviors of adhesivelybonded joints between FRP sandwich decks and steel girders before hygrothermal aging. A specific tensile-shear loading device was designed with the capacity to provide the combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…All failure mechanisms that were identified correspond to those already presented by other authors in previous research works [33][34][35][36][37][38][39]. However, only 6 of the 34 specimens failed by a single dominant mechanism, while the other 28 developed combined failure modes, characterized by two or three failure patterns.…”
Section: Characteristic Failure Modes and The Corresponding Ultimate Loadssupporting
confidence: 83%
“…All failure mechanisms that were identified correspond to those already presented by other authors in previous research works [33][34][35][36][37][38][39]. However, only 6 of the 34 specimens failed by a single dominant mechanism, while the other 28 developed combined failure modes, characterized by two or three failure patterns.…”
Section: Characteristic Failure Modes and The Corresponding Ultimate Loadssupporting
confidence: 83%
“…According to the instruction of CBSR-A/B and Table 4, the ingredients and properties are similar to the adhesive BUFA-BONDING PASTE 740-0110 applied in our previous researches on FRP-to-steel joint Bijlaard 2013, 2014;Jiang et al 2015aJiang et al , 2015b, which properties have been already studied. In China, CBSR-A/B is massively available in the market, however, there was no related adhesive parameter when it was applied between GFRP and steel, and the manufacturer of CBSR-A/B could not provide them, either.…”
Section: Gfrp Panels and Purlins Connectionmentioning
confidence: 88%
“…The weakest region of composite structures is the interface unit between the composite element and the metal/composite member bonded using epoxy resin adhesives. Therefore, considerable research has been conducted to investigate the fatigue performance of adhesive interface units, mostly on fiber reinforced plastics (FRP) composite joints [3][4][5][6][7][8][9][10]. It was suggested that more research should be conducted to understand bonded joint behavior and to improve joint design [11].…”
Section: Introductionmentioning
confidence: 99%